2014
DOI: 10.5717/jenb.2014.18.1.69
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a single bout pilates exercise on mRNA expression of bone metabolic cytokines in osteopenia women

Abstract: [Purpose]The purpose of this study was to examine the effect of a single bout pilates exercise on mRNA expression of bone metabolic cytokines in elderly osteopenia women.[Methods]We selected 11 people of elderly osteopenia women and loaded a single bout pilates exercise about RPE 10-14 level. The blood samples were collected before, immediately after and 60 minute after pilates exercise, then examined calcium metabolic markers in serum and extracted peripheral blood mononuclear cell (PBMC) from whole blood and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…It is judged that the Pilates exercise in the present study qualifies as highly intensive exercise which may cause muscle damage unlike the aerobic exercise performed in prior studies. A previous study performed by the authors on seniors [ 6 ] showed a 1.4x increase in the CK index after one-time Pilates exercise, indicating that the exercise was vigorous enough to cause muscle damage. The current study found that the CK index increased by about 1.9 times after 8 weeks of Pilates exercise.…”
Section: Discussionmentioning
confidence: 99%
“…It is judged that the Pilates exercise in the present study qualifies as highly intensive exercise which may cause muscle damage unlike the aerobic exercise performed in prior studies. A previous study performed by the authors on seniors [ 6 ] showed a 1.4x increase in the CK index after one-time Pilates exercise, indicating that the exercise was vigorous enough to cause muscle damage. The current study found that the CK index increased by about 1.9 times after 8 weeks of Pilates exercise.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Balaji et al ( 52 ) and Tang et al ( 53 ) also demonstrated improved TC/HDL ratios in yoga practitioners and attributed this to increased intracellular levels of hepatic lipase, lipoprotein lipase metabolism, and a successive increase in uptake of triglycerides by adipose tissue. Similarly, 12 weeks of yoga practice were found to reduce fasting blood glucose levels and improve lipid profiles in polycystic ovary syndrome (PCOS) ( 54 , 55 ). To our knowledge since there are varying types of yoga practices, it is difficult or indeed impossible to delineate the benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The researcher designed the registration forms for the measurements of the research, so it has the simplicity, ease, accuracy and speed of registration: Table (4) shows the tests that obtained 80% or more of the views of the experts…”
Section: Data Registration Formsmentioning
confidence: 99%